El acoso laboral en el Ecuador: un enfoque desde los derechos humanos - Tandazo Gallegos, Nery Martin (2024)
Workplace harassment in Ecuador has a considerable impact on the workers’ quality life and professional performance, being produced by several issues that affect their work environment. Approaching this problematic from a human rights perspective is essential to improve the workers’ welfare and integrity, as well as to promote an equitable and respectful work environment. Having specified the above, the present research work had the objective of determining if the workplace’s harassment figure in the Ecuadorian legal system violates human rights and constitutional guarantees. For this purpose, a theoretical investigation was carried out with a qualitative descriptive approach. The selected methods were deductive and exegetical. To collect data, some research techniques were implemented, including direct observation, content analysis, and the study of judicial judgments. Finally, the gotten results indicate that, despite the ratification of international human rights instruments by the Ecuadorian State to protect workers against workplace harassment, internal legislation does not comply with international standards; since it does not considerspecific sanctionsfor this behavior. In contrast, both Chile and Colombia there are legal provisions that penalize this conduct in the workplace ambit. On the other hand the complaints are more common in the public sector due to specialized regulations, while in the private sector they are limited due to fear of job loss. Consequently, due to the lack of public labor policies in Ecuadorian legislation, it is proposed to introduce workplace harassment as a contravention in the Comprehensive Organic Penal Code; taking into account that in the labor code it appears as a cause for approval in the administrative field.